PENGARUH PENERAPAN APLIKASI GAME EDUKASI QUIZIZZ TERHADAP PENINGKATAN HASIL BELAJAR SISWA SEKOLAH DASAR - Mauludia, Salsa Mei; Rezania, Vanda (JURNAL PENDIDIKAN DASAR PERKHASA: Jurnal Penelitian Pendidikan Dasar, 2026)
This study aimed to improve elementary students’ learning outcomes through the use of Quizizz as a learning medium. The research was conducted at SDN Candipari II Porong using a quantitative approach with a true experimental design, specifically a pretest–posttest control group design. The sample consisted of 40 fourth-grade students selected through simple random sampling. Data were collected using a multiple-choice test instrument. The results showed that the experimental group using Quizizz achieved higher posttest scores compared to the control group, which was taught using the lecture method. The implementation of Quizizz as a game-based learning application had a significant positive effect on students’ learning outcomes. It also strengthened students’ cognitive skills through an interactive and enjoyable gamification approach. The success of this method was influenced by active student participation in games and competition, which increased their enthusiasm during the learning process. In conclusion, Quizizz is an effective digital learning medium for enhancing elementary students’ learning outcomes and engagement.